Analisis Pengawasan Kekuasaan Pemerintah dalam Perspektif Hukum Tata Negara Indonesia - Muhammat Davi; M. Aditya Yusuf (YASIN, 2026)
The urgency of oversight over government power has become increasingly critical in the administration of the modern state, which is vulnerable to the abuse of authority and uncontrolled executive discretion. Although previous studies have examined government oversight from the perspectives of administrative law and institutions, these studies tend to be partial and have not integrated legislative oversight, judicial review, and internal oversight mechanisms into a holistic constitutional law framework. This study aimed to analyze the mechanisms for overseeing government power in the Indonesian constitutional law system, evaluate their effectiveness in preventing the abuse of power, identify juridical obstacles, and formulate recommendations for improvement. This study used a normative juridical method with statutory, conceptual, and comparative approaches. Data were collected through a literature review of primary, secondary, and tertiary legal materials from the 2016–2024 period and then analyzed through the stages of inventory, systematization, norm interpretation, and legal construction. The study was conducted from January to August 2024. The results showed that the Indonesian constitutional law system has provided a comprehensive normative framework for oversight through legislative oversight by the DPR, judicial oversight by the Constitutional Court and the Supreme Court, as well as external and internal oversight through the BPK, the Ombudsman of the Republic of Indonesia, and APIP. However, the effectiveness of oversight still faces significant weaknesses, as indicated by 29% of BPK audit recommendations not being followed up, Indonesia’s Corruption Perceptions Index score of 34/100 with a ranking of 115/180, and the continued compromise of the institutional independence of supervisory bodies. The conclusion of this study emphasizes that although a comprehensive normative framework for oversight is already available, its effectiveness remains hindered by regulatory disharmony, limited institutional independence, and procedural complexity. This study contributes by offering a reconstruction of an oversight framework based on integrative constitutionalism through regulatory harmonization in an umbrella law, strengthening the executorial authority of the Ombudsman of the Republic of Indonesia, and modernizing the oversight system through technology-based e-monitoring.